2018
DOI: 10.2147/cmar.s164677
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymph node metastases in salivary gland adenoid cystic carcinoma: a systematic review and meta-analysis

Abstract: BackgroundThe purpose of this research was to determine whether neck dissection is necessary for the adenoid cystic carcinoma (ACC) of head and neck.Materials and methodsThis article screened the abstract and full-text papers that investigated salivary gland primary ACC of head and neck. Two independent reviewers searched for articles published before October 2017 in three databases (Web of Science, PubMed, and Ovid), having no limits in date and language. Statistical data were analyzed statistically by Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
1
11
1
Order By: Relevance
“…In our series, the cN þ rate at the time of diagnosis is low (11%, 48 patients). In comparison, Ning's meta-analysis finds a high variability of results (4%e33%) depending on the series, with an average of 16% of cNþ [13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our series, the cN þ rate at the time of diagnosis is low (11%, 48 patients). In comparison, Ning's meta-analysis finds a high variability of results (4%e33%) depending on the series, with an average of 16% of cNþ [13].…”
Section: Discussionmentioning
confidence: 95%
“…Few studies present the occurrence rate of occult LNM among the cN0 after ND. It varies from 8% to 23%, with an average of 14% in Ning's meta-analysis [7,13,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] Ning et al performed a systematic review and reported that the average rate of occult metastasis in salivary gland ACC was 14%. [ 37 ] Xiao et al reviewed the United States National Cancer Database and reported that cN0 patients with ACCs in the major salivary glands and tongues had significantly increased risk of occult metastasis, and they suggested that prophylactic neck dissection is necessary for this group. [ 38 ] In contrast, a recent multi-institutional retrospective analysis in Japan showed that prophylactic neck dissection for the salivary glands ACC was not associated with better clinical outcomes in the 5 year observation periods.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural and lymphovascular invasion, as well as extracapsular spread, are well known adverse pathological characteristics [1518]. Walvekar et al [7] reported that high grade parotid cancer is more likely to exhibit extracapsular spread.…”
Section: Discussionmentioning
confidence: 99%